Pesquisa de mutações em pacientes com Glomeruloesclerose Segmentar e Focal Familiar ou Síndrome Nefrótica Esteroide Resistente - Riguetti, Michelle Tiveron Passos [UNIFESP] (2016)
Introduction : Focal segmental glomerulosclerosis (FSGS) and the steroid-resistant nephrotic syndrome (SRNS) can be caused by mutations in the genes encoding proteins that are essential for normal podocyte structure and/or function. Mutations in the podocin gene cause a recessive form of SRNS. Affected patients were characterized by early-onset disease whereas mutation in ACTN4, INF2 and TRPC6 genes cause a dominant form of familial FSGS presenting in adolescence or early adulthood. Objectives : We aimed to implement and carry out the research of mutations in the genes NPHS2, ACTN4, INF2 and TRPC6 in patients with familial FSGS or SRNS in our service. Material and Methods : This study was performed in six Brazilian index-patients and their families, totalizing fifteen individuals. The index-patients had SRNS or biopsy-proven FSGS (3 males and 3 females, mean ages of 30.7 ± 16.7, and at the time of diagnosis 17 ± 14.9 years). All patients were steroid-resistant. Genomic DNA was isolated from peripheral blood lymphocytes using DNAzol®. Amplification of all exons of the ACTN4, INF2, NPHS2 and TRPC6 genes was carried out by polymerase chain reaction (PCR) using Taq polymerase and the oligonucleotide primers were previously designed. The products of PCR were purified and the DNA was sequenced directly by use of the BigDye Terminator v3.1 Cycle Sequencing. Results : We have found mutations in five of the six index-patients and their families. R229Q has been identified as a polymorphism in association with the deleterious mutations S313L, P316S and R291W in the NPHS2 gene and with G894S in the ACTN4 gene. It was also detected only the polymorphism A404V in the TRPC6 gene in three members of a family. The polymorphism rs10133301 in the INF2 gene was found in five of the six patients index. Conclusions : It was possible to establish in our service the methodology for mutations research in NPHS2, ACTN4, TRPC6 and INF2 genes related to SRNS and familial FSGS, as well as to standardize the methodology and apply it to the study of 15 members of six families with such diseases. Mutations in the NPHS2 gene were the most frequent, as well as the presence of the R229Q polymorphism (which associated with a mutation leads to greater severity and progression to end stage renal disease) in this group of patients. Two of the mutations found in the NPHS2 gene (S313L and P316S) had not been described previously.